2012
DOI: 10.1016/j.bjid.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin serum concentrations in pediatric oncologic/hematologic intensive care patients

Abstract: Higher than usual vancomycin doses may be required to treat staphylococcal infections in children with oncologic/hematologic diseases. Since the best known predictor of efficacy is the AUC/MIC ratio, serum trough concentrations must be analyzed in conjunction with MICs of prevalent Staphylococci and pharmacokinetic tools such as Bayesian analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…A total of 17 studies reporting PK-parameters of vancomycin in critically ill children were identified by the search, with more than 1000 PICU patients included in total over the whole pediatric age range [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Most studies included a mixed population, but also specific populations (such as patients with hematologic/oncologic [43,45], cardiac [51,53,56,57], traumatic [50] and infectious diseases [44,48]) being studied separately. Four studies [42,43,46,48] were prospective PK studies and the remaining 13 studies were based on TDM data.…”
Section: Vancomycinmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 17 studies reporting PK-parameters of vancomycin in critically ill children were identified by the search, with more than 1000 PICU patients included in total over the whole pediatric age range [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Most studies included a mixed population, but also specific populations (such as patients with hematologic/oncologic [43,45], cardiac [51,53,56,57], traumatic [50] and infectious diseases [44,48]) being studied separately. Four studies [42,43,46,48] were prospective PK studies and the remaining 13 studies were based on TDM data.…”
Section: Vancomycinmentioning
confidence: 99%
“…Most studies used intermittent dosing with daily doses of vancomycin ranging from 30 to 60 mg/kg/day, with only 1 study reporting higher mean doses (81 mg/kg/day) [45] and 1 study not mentioning the dose at all [41]. Two studies reported data on continuous dosing schedules, using a loading dose of 15 mg/kg and a maintenance dose of 40-45 mg/ kg over 24 h [42,55].…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Since current practice relies on trough-only monitoring, the Bayesian approach would be a more conducive option. Other advantages include the program's ability to account for changes in PK profiles and reduce the risk of trough concentrations [20 lg/mL [8,10]. Several validated software programs with Bayesian analysis capabilities such as BestDose TM , MwPharm Ó , and T.D.M.S 2000 TM are available to clinicians, and are currently being used clinically for therapeutic drug monitoring purposes [11].…”
Section: Pediatric Vancomycin Efficacy: How Should Wementioning
confidence: 99%
“…With standard dosing of 40-60 mg/kg/day, the achievement rate decreased to 50 %. Patients were observed to have increased vancomycin clearance and increased volume of distribution, suggesting that pediatric oncology patients with normal renal function need higher vancomycin dosing to achieve the target AUC/MIC compared with otherwise healthy children [10]. Other populations to consider examining for altered vancomycin PK are critically ill, burn, and cardiac patients.…”
Section: Vancomycin Use: Differences In Special Populationsmentioning
confidence: 99%